Ajaran Yoga Dalam Teks Dharma Pātañjala dan Implementasinya di Perguruan Ananda Marga Yoga Denpasar - Yoga Wiyana; I Ketut Donder; Hari Harsananda (UHN IGB Sugriwa Denpasar, 2022)
The Dharma Pātañjala text is a text that formulates Yoga teachings which are similar to the teachings of the Yoga Sutras of Patanjali. Ananda Marga Yoga as one of the Yoga schools in Bali which is still implementing Yoga teachings known as Rajadhiraja Yoga. The discussion in this study is the structure of Yoga teachings in the Dharma Pātañjala text, the implementation of Yoga teachings in the Dharma Pātañjala text at Ananda Marga Yoga colleges, and the implications of Yoga teachings in the Dharma Pātañjala text for the Ananda Marga Yoga school. This study uses the theory of structure, hermeneutics, symbolic interactionism, and the theory of reciprocity. The results of the study include the structure of the teachings of Yoga in the Dharma Pātañjala text explained about Samādhi, Yoga levels, Japa Pranava OṀ, obstacles that will be encountered by Yogis, Panca Kleśa, Prayogasandhi or Aṣṭāṅga Yoga consisting of Yama, Niyama, sana, Pratyāhāra, Prāṇāyāma, Dhāraṇā, Dhyāna, and Samādhi and Samyaṁa techniques. The implementation of the Yoga teachings contained in the Dharma Pātañjala text and carried out at the Ananda Marga Yoga school is a system of Yoga teachings known as Rajadhiraja Yoga. Rajadhiraja Yoga is an extension of the ancient Raja Yoga system or Aṣṭāṅga Yoga. As well as the implications of Yoga teachings that are useful for improving health, increasing spiritual awareness and intelligence, maintaining harmony in life, and self-control systems.